Design On The Go: How African American youth use mobile technologies for digital content creation - Harris, Ronah (Design and Technology Education: An International Journal, 2010)
The use of mobile technologies has been proposed for increasing access and designing innovative educational activities. Unfortunately, there is limited data on the current uses of cellular phones amongst low-income African American youth. In particular, there is little known about how this population may design on the rapidly adapting technology, what digital content they create and share via mobile technology. In this exploratory study, I surveyed 103 youths, ages 13-21, and asked about their ownership of cellular phones and their patterns of use with media, the Internet, as well as whether they create digital content. The findings indicate that although these young people use many forms of technology and media, they are more prone to creating content such as photographs and share their writing through cellular phones than through the Internet. The results of this study may indicate trends in use and the opportunity to develop and support digital design and content on mobile platforms.